The last boyfriend - Roberts, Nora.; Roberts, Nora. Inn BoonsBoro trilogy (New York : Berkley Books, 2012)
Working alongside his mother and brother restoring a historic hotel in Boonsboro, Maryland, Owen Montgomery falls for a childhood friend.
Includes an excerpt from The Perfect Hope, the third book in the Inn BoonsBoro trilogy.
Keywords: First loves -- Fiction; Mothers and daughters -- Fiction